Emerging Soluble Protein Markers in Colorectal Cancer (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
Small soluble proteins that are part of immune regulation such as cytokines, chemokines and growth factors are significantly involved in the pathogenesis of cancers. Their increase concentration in biological fluids and tissues suggest pathway activation that involves in inflammatory response or cancer progression. The knowledge of these soluble proteins has increasing clinical importance as a biomarker tool in screening, diagnosis classification, therapeutic surveillance and intervention. The review gives a short insight into the most commonly reported cytokines, chemokines and growth factors and their potential roles in the carcinogenesis. We discuss recent findings on their functions in colorectal carcinoma through analysis of their expression patterns, the use of selective inhibitors and signaling pathways involved.
Keywords: Cytokines, chemokines, colorectal carcinoma, interleukins, expression